KARANGANYAR BATIK AS A CULTURAL EDUCATION MEDIA - Mega Reforma; Agung Yuliyanto Nugroho; Moch Nur Syamsu (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the management of batik as an educational tourism attraction based on local cultural values in Karanganyar Regency, with an emphasis on the involvement of the five key actors in the Penta Helix model—government, academia, business sector, community, and media. Karanganyar possesses rich cultural heritage in the form of batik, which holds significant potential to be developed into an educational tourism destination. However, its current management still faces various challenges. This research employed a qualitative descriptive approach, using in-depth interviews, field observations, and document studies for data collection. Data were analyzed using thematic analysis, referring to destination management theory (Cooper et al., 2008) and the concept of edu-tourism (Bodger, 1998). The results reveal that the management of batik educational tourism in Karanganyar has not yet been systematically integrated. Key issues identified include: (1) limited human resources with adequate competence, (2) conventional tourism practices, (3) lack of innovation in tourism product packaging, (4) insufficient institutional coordination and support, and (5) underdeveloped integration between cultural and educational tourism. While there is a strong commitment to cultural preservation from local communities and participation from business actors, structural support from the government and optimization of the media’s role require further enhancement. The implication of this research emphasizes the need for strengthened cross-sectoral collaboration through the Penta Helix framework, the formulation of specific policies for educational tourism development, as well as innovations in digital promotion and context-based cultural education curricula. This study is expected to serve as a reference for policymakers, tourism practitioners, and future researchers in promoting sustainable educational tourism rooted in local culture.